2021
DOI: 10.1038/s41467-020-20702-2
|View full text |Cite
|
Sign up to set email alerts
|

Rab1-AMPylation by Legionella DrrA is allosterically activated by Rab1

Abstract: Legionella pneumophila infects eukaryotic cells by forming a replicative organelle – the Legionella containing vacuole. During this process, the bacterial protein DrrA/SidM is secreted and manipulates the activity and post-translational modification (PTM) states of the vesicular trafficking regulator Rab1. As a result, Rab1 is modified with an adenosine monophosphate (AMP), and this process is referred to as AMPylation. Here, we use a chemical approach to stabilise low-affinity Rab:DrrA complexes in a site-spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 64 publications
(57 reference statements)
0
18
0
Order By: Relevance
“…30 First, in an in vitro reaction of the well-described pair of AMP-transferase DrrA and its substrate Rab1b with ATP or N 6 -propargyl ATP the AMPylated Rab1b was prepared and characterized by intact protein MS (Figure S5 and S6). 31,32 Both, wt and N 6 -propargyl modified proteins were then coupled with DMP-tag, reduced, alkylated and trypsinized. The resulting peptide mixture was analyzed by direct injection into the mass spectrometer.…”
Section: Resultsmentioning
confidence: 99%
“…30 First, in an in vitro reaction of the well-described pair of AMP-transferase DrrA and its substrate Rab1b with ATP or N 6 -propargyl ATP the AMPylated Rab1b was prepared and characterized by intact protein MS (Figure S5 and S6). 31,32 Both, wt and N 6 -propargyl modified proteins were then coupled with DMP-tag, reduced, alkylated and trypsinized. The resulting peptide mixture was analyzed by direct injection into the mass spectrometer.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we have tested the possibility to capture the monophosphate moiety of AMPylated proteins using an alkoxide-bridge Mn 2+ metal complex bound in the gel by Phos-tag ligand. We have used a recombinant Rab1b protein, which was AMPylated in vitro by the recombinant bacterial effector DrrA ( Du et al., 2021 ). The Rab1b identities were confirmed by top-down mass spectrometry ( Figure S4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Cosubstrate mediated cross-linking not only helped to study substrate recognition of enzymes but also served to identify an unexpected enzymatic activation mechanism of the Legionella effector DrrA/SidM . As mentioned before, DrrA is a multidomain effector enzyme secreted to host cytosol during infection and interferes with membrane trafficking via its GEF and AMP transfer activities toward the human small GTPase Rab1. , While the concept of genetic code expansion allowed structural insights to be obtained on DrrA GEF activity by cross-linking DrrA GEF –Rab1 (as discussed in section ), the molecular details on AMP transfer by the ATase domain (DrrA ATase ) were incomplete .…”
Section: Structure Stabilization Via Cross-linking Based On Enzyme Ca...mentioning
confidence: 99%
“…As mentioned before, DrrA is a multidomain effector enzyme secreted to host cytosol during infection and interferes with membrane trafficking via its GEF and AMP transfer activities toward the human small GTPase Rab1. , While the concept of genetic code expansion allowed structural insights to be obtained on DrrA GEF activity by cross-linking DrrA GEF –Rab1 (as discussed in section ), the molecular details on AMP transfer by the ATase domain (DrrA ATase ) were incomplete . In a recent study, the covalently linked DrrA ATase –Rab1 complex was obtained which allowed successful structure determination by X-ray crystallography . Surprisingly, the complex structure revealed that Rab1 was unexpectedly cross-linked to the backside instead of the catalytic site of DrrA ATase .…”
Section: Structure Stabilization Via Cross-linking Based On Enzyme Ca...mentioning
confidence: 99%